Editorial Letter| Dossier 19: Methodology in Design, Engineering, Product Design, Textile Materials, and Education (Revista de Ensino em Artes, Moda e Design, 2025)
This Editorial Letter introduces Dossier 19: Methodology in Design, Engineering, Product Design, Textile Materials, and Education from the Revista de Ensino em Artes, Moda e Design, published in October 2025. In their text, the organizers – Lais Kohan, Ivis de Aguiar Souza, and Júlia Baruque-Ramos – contextualize the importance of transdisciplinary integration among Design, Engineering, Education, and Textile Materials for solving complex problems in contemporary society.The dossier is organized into four main sections, which highlight a coordinated reflection on: 1. Design Theory and Methodology – serving as the foundation for understanding and organizing creative and design processes to guide both practice and teaching; 2. Design Education – which translates these methodologies into transdisciplinary teaching and learning methods to develop critical professionals capable of navigating complex contexts; 3. Digital Design Methods – which act as empowering tools through the introduction of technologies such as AI, 3D modelling, and additive manufacturing; 4. Textile Materials and Textile Product Design Engineering – where the integration of design, engineering, and sustainability materializes in the development of innovative textile products, ranging from biodegradable materials to structures for healthcare and fashion applications. Together, these axes demonstrate how contemporary design articulates knowledge, technology, education, and materiality to address the socio-environmental and technological challenges of our time.
Keywords: design theory and methodology; digital design methods; textile materials; textile product design engineering